Desmoid with biweekly methotrexate and vinblastine shows similar effects to weekly administration: A phase II clinical trial. Issue 11 (5th September 2020) - Nishida, Yoshihiro; Hamada, Shunsuke; Urakawa, Hiroshi; Ikuta, Kunihiro; Sakai, Tomohisa; Koike, Hiroshi; Ito, Kan; Emoto, Ryo; Ando, Yuichi; Matsui, Shigeyuki
Abstract: Low‐dose methotrexate (MTX) plus vinblastine (VBL) chemotherapy is an effective treatment for desmoid‐type fibromatosis (DF). However, previous reports have described a weekly regimen, with no reports available on a biweekly one. The aim of this study was to determine the clinical outcomes of a biweekly regimen in a cohort prospectively treated in our single institution. Since 2010, we have prospectively treated refractory DF patients with biweekly MTX (30 mg/m 2 ) + VBL (6 mg/m 2 ). Efficacy, progression‐free survival (PFS), and correlating factors were analyzed. Adverse events (AEs) were recorded. In total, 38 patients received low‐dose MTX + VBL therapy, and its efficacy was assessed in 37 of them. Nineteen (51%) patients showed partial response (PR). Clinical benefit rate was 95%. PFS at 5 y was 80.8%. In PR cases, median time to response was 10 mo. Longer duration of therapy was significantly associated with the response of PR ( P  = .007) by univariate analysis. There was no clear association between various clinicopathological factors, including tumor size, location, catenin beta‐1 ( CTNNB1 ) mutation status with effect. Only 3 AEs of grade 3/4 were observed. Tumor regrowth after MTX + VBL discontinuation was observed in 5 (20%) of 25 patients. Biweekly administration of MTX + VBL chemotherapy was well tolerated compared with weekly administration, and its efficacy was anticipated in DF patents, although the time needed to achieve a response may be relatively long. The treatment interval should be determined taking into account both the condition of the tumor and the patient's preference. Abstract : Biweekly administration of MTX + VBL chemotherapy for desmoid patients was well tolerated compared with weekly administration, and its efficacy was similar. The time needed to achieve a response may be relatively long with a biweekly regimen.